Text sophistication and sophisticated investors - JOENVAARA, Juha (Institutional Knowledge at Singapore Management University, 2019)
We show that two novel measures of text sophistication, applied to hedge fund strategy descriptions, encapsulate incremental information about funds. Consistent with the linguistics literature, hedge funds with lexically diverse strategy descriptions outperform, eschew tail risk, and encounter fewer regulatory problems. In line with the literature, hedge funds with syntactically complex strategy descriptions report more regulatory violations and trigger more severe infractions. Fund investors recognize the dichotomy and direct flows accordingly, but not enough to erode away the alphas of lexically diverse funds. Our findings suggest that text sophistication measures provide texture on the cognitive ability and trustworthiness of sophisticated investors.